Determinants of foreign direct investment in renewable electricity industry in Africa. Issue 8 (14th September 2022) - Rashed, Ahmed; Yong, Chen-Chen; Soon, Siew-Voon
ABSTRACT: Using a novel dataset of foreign direct investment (FDI) corporations in the renewable electricity industry (REI), coupled with a large range of employed variables, this paper empirically examines FDI determinants in the REI in Africa between 2003 and 2019. The electricity insecurity issues worsen daily, aggravating all facets of African life. A range of promising and informative results were found using the FDI panel gravity fixed effects Poisson pseudo-maximum likelihood model. Interestingly, we reveal the uselessness of fossil fuel subsidy changes in stimulating green FDI in Africa. However, a 1% growth in Africa's gross domestic product expands FDI by almost 1.5%. Similarly, one additional point in the corruption index reduces FDI by about 1.2%. Furthermore, increasing the number of educated African children and raising renewable energy awareness contributes constructively to the REI and sustainable energy development. To mitigate the energy issues, policymakers should elevate clean power consciousness among Africans and enhance sustainable energy support and policies.